(untitled) (Journal of International Relations and Peace, 2025)
This study explores the intersection of disinformation, hate speech, and social media in shaping conflict dynamics, with a specific focus on Sudan’s civil strife. Examines how online narratives fuel group violence and exacerbate political instability using qualitative research methods, including content and discourse analysis. Data Collection sources based on secondary data from publications between May 2010 to 2023, including academic articles and policy reports, which offer historical insights into Sudan’s conflicts, particularly during the Darfur crisis. In addition, the study includes policy reports from organizations such as the United Nations and Human Rights Watch to contextualize the Role of hate speech and disinformation in fragile states. The study focuses on two primary case studies: The Darfur Conflict and the SAF-RSF Conflict. These case studies explore how hate speech and disinformation are used to manipulate public perception and escalate ethnic tensions, mainly through digital platforms. They also examine community-level responses to these narratives and their impact on peacebuilding initiatives.